What primary health‐care services are Australian consumers willing to accept from nurse practitioners? A National Survey. (11th July 2012) - Parker, Rhian; Forrest, Laura; McCracken, James; McRae, Ian; Cox, Darlene
Abstract Background Nurses are becoming increasingly important as providers of primary health care in Australia. In November 2010, Medicare provider rights and Pharmaceutical Benefits Scheme rights for nurse practitioners, working in private practice and in collaboration with a medical practitioner, were introduced in Australia. Although international evidence suggests that nurse practitioners would be appropriate and acceptable providers of care at the first point of contact, such as primary health care, there is little Australian evidence about what care consumers are willing to accept from nurse practitioners. Objectives To ascertain what care Australian health‐care consumers would accept from nurse practitioners in this setting. Participants Australian adults over 18 years of age. Methods National Survey delivered online. Information about the survey was disseminated through a media campaign, stakeholder engagement and through the health‐care consumer networks nationally. Results The total number of respondents that started the survey was n = 1883. Ninety‐five percentage (n = 1784) of respondents completed the survey. The majority of respondents were women, aged 25–54 years, had completed tertiary education and had an annual household income of more than A80 000. The majority of the respondents (n = 1562, 87%) said they would be prepared to see a nurse practitioner for some of their primary health‐care needs. Conclusions The findings of this study suggest consumers are accepting of a range of activities undertaken by nurse practitioners in primary health care and this has relevance for primary health‐care workforce mix and organization, particularly for areas that are underserved by medical practitioners.